Response of cowpea germplasm to bacterial blight in Uganda - Nantale, Gauden; Wasswa, Peter; Tusiime, Richard; Muhumuza, Edgar; Dramadri, Isaac Onziga; Paparu, Pamela (Journal of Scientific Agriculture, 2023)
Cowpea (Vigna unguiculata (L.) walp) is a legume crop mainly grown on small scale in low–input farming systems in Uganda. Cowpea bacterial blight (CoBB) disease caused by Xanthomonas axonopodis pv. vignicola (Burkh.) Dye is increasingly becoming a major hindrance to cowpea productivity. Sixty-four cowpea genotypes were evaluated for their response to bacterial blight disease (CoBB). Field experiments were carried out during the first and second rainy seasons using alpha lattice design with three replications. Data on disease incidence and severity, grain yield, days to 50% flowering, number of seeds per pod, pod length, number of peduncles per plant, and number of branches per plant were collected. Disease severity and incidence data was used to determine relative Area Under Disease Progress Curve (rAUDPC). Results showed significant differences (P ≤ 0.001) among the genotypes for rAUDPC in each season. The rAUDPC across the seasons indicated that genotypes NE 32, WC 32A, WC 26 and NE 44 with rAUDPC values ranging from 0.22 to 0.26 were resistant to CoBB whereas genotypes NE 31 and NE 40 with rAUDPC values 0.44 and 0.46 respectively were susceptible. The rAUDPC did not show any significant correlation with days to 50% flowering, yield and its components. This study suggested that the genotypes NE 32, WC 32A, NE 44, and WC 26 be used as prospective parents in breeding initiatives to develop bacterial blight-resistant varieties due to their high yields and resistance to CoBB.